LITERATURE REVIEW DETERMINATION OF EMPLOYEE SATISFACTION AND PERFORMANCE: HYGIENE AND MOTIVATOR FACTORS ANALYSIS - Basril, Hasan (Dinasti International Journal of Management Science, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews job satisfaction and employee performance: Analysis of Hygiene Factors and Motivator Factors, A Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are that: 1) Hygiene factors affect job satisfaction; 2) Motivator factors affect job satisfaction; 3) Hygiene factors affect employee performance; 4) Motivator factors affect employee performance; and 5) Job satisfaction has an effect on employee performance.